Engineering amphiphilic nanofiltration membrane surfaces with a multi-defense mechanism for improved antifouling performances. Issue 20 (4th May 2016) - Zhang, Runnan; Li, Yafei; Su, Yanlei; Zhao, Xueting; Liu, Yanan; Fan, Xiaochen; Ma, Tianyi; Jiang, Zhongyi
Abstract : Amphiphilic nanofiltration membrane surfaces with a multi-defense (hydrophilic fouling-resistant and hydrophobic fouling-release) mechanism were engineered and exhibited improved antifouling performances against various foulants. Abstract : Antifouling nanofiltration (NF) membrane surfaces capable of combating membrane fouling caused by different foulants are highly desirable for their broad applications. In this study, amphiphilic NF membranes with both hydrophilic domains and low surface energy domains were prepared to optimally integrate the fouling-resistant defense mechanism and fouling-release defense mechanism for enhanced antifouling performance. The construction of amphiphilic surfaces involved two-step surface modification of the hydrophilic polyamide NF membrane: (1) the introduction of primary amine groups as active sites by grafting triethylenetetramine (TETA) onto the carboxyl groups of the polyamide membrane; (2) the subsequent grafting of 2, 2, 3, 4, 4, 4-hexafluorobutyl methacrylate (HFBM) through the Michael addition reaction. The amphiphilic membranes had better antifouling properties compared with the hydrophilic polyamide membrane during the filtration of bovine serum albumin (BSA) protein solution, humic acid solution and oil/water emulsion, which exhibited lower flux decline during utilization and higher flux recovery after water cleaning. Hopefully, this study is applicable to prepare a broad spectrum of antifouling NF membranes.